2017
DOI: 10.1093/hmg/ddx294
|View full text |Cite|
|
Sign up to set email alerts
|

DJ-1 is a redox sensitive adapter protein for high molecular weight complexes involved in regulation of catecholamine homeostasis

Abstract: DJ-1 is an oxidation sensitive protein encoded by the PARK7 gene. Mutations in PARK7 are a rare cause of familial recessive Parkinson’s disease (PD), but growing evidence suggests involvement of DJ-1 in idiopathic PD. The key clinical features of PD, rigidity and bradykinesia, result from neurotransmitter imbalance, particularly the catecholamines dopamine (DA) and noradrenaline. We report in human brain and human SH-SY5Y neuroblastoma cell lines that DJ-1 predominantly forms high molecular weight (HMW) comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…J. Larsen et al, 2011; Thomas et al, 2011), protein transcription and processing (Takahashi et al, 2001; Shinbo et al, 2005; J. Xu et al, 2005; Zhong et al, 2006; Lu et al, 2016;), neurotransmitter reuptake (Luk et al, 2015; Piston et al, 2017), proteasome activity (Saito et al, 2016; Moscovitz et al, 2017), and signal transduction (Aleyasin et al, 2010; Zhang et al, 2017; reviewed in Oh and Mouradian, 2017), abnormalities of which are implicated in the pathogenesis of PD. A highly conserved (S. Bandyopadhyay and Cookson, 2004; Bai et al, 2006;), and readily oxidized cysteine (Cys)106 residue suggests that DJ-1 functions in part as a redox sensor (Canet-Avilés et al, 2004; Taira et al, 2004; Kinumi et al, 2004; Ooe et al, 2006; Blackinton et al, 2009b), and is induced in substantia nigra (SN) dopamine neurons that experience a high degree of oxidative burden (Lin and Beal, 2006; X.…”
Section: Introductionmentioning
confidence: 99%
“…J. Larsen et al, 2011; Thomas et al, 2011), protein transcription and processing (Takahashi et al, 2001; Shinbo et al, 2005; J. Xu et al, 2005; Zhong et al, 2006; Lu et al, 2016;), neurotransmitter reuptake (Luk et al, 2015; Piston et al, 2017), proteasome activity (Saito et al, 2016; Moscovitz et al, 2017), and signal transduction (Aleyasin et al, 2010; Zhang et al, 2017; reviewed in Oh and Mouradian, 2017), abnormalities of which are implicated in the pathogenesis of PD. A highly conserved (S. Bandyopadhyay and Cookson, 2004; Bai et al, 2006;), and readily oxidized cysteine (Cys)106 residue suggests that DJ-1 functions in part as a redox sensor (Canet-Avilés et al, 2004; Taira et al, 2004; Kinumi et al, 2004; Ooe et al, 2006; Blackinton et al, 2009b), and is induced in substantia nigra (SN) dopamine neurons that experience a high degree of oxidative burden (Lin and Beal, 2006; X.…”
Section: Introductionmentioning
confidence: 99%
“…Despite not being enzymes of the cellular antioxidant system, GAPDH, DJ-1, TG2, and CypA are all differentially expressed in response to oxidative stress (78), and there is some evidence to support crossregulatory influences in transcription of these moonlighting proteins in response to stress conditions. In human neuroblastoma cell lines expressing a mutant overoxidant mimic of DJ-1 (C106DD), expression of TG2 was downregulated and ASK1 upregulated relative to cells containing wild-type DJ-1 (285), and astroglial DJ-1 overexpression has been shown to relate to upregulation of CypA (102). The ''polygamous'' influence of these moonlighting proteins cannot be understated and a further spectrum of complexity can arise from functional interactions between the moonlighting proteins themselves, such as TG2 transamidating GAPDH (152) and DJ-1 deglycating the glycated form of GAPDH (304).…”
Section: Discussionmentioning
confidence: 99%
“…DJ-1 shown to be a redox sensitive adapter protein for high molecular weight complexes involved in regulation of catecholamine homeostasis, specifically noradrenaline and dopamine (Fig. 1 ) (Piston et al 2017 ).…”
Section: Structure Functions and Mechanism Of Dj-1 Actionmentioning
confidence: 99%
“…Recent studies have shown that DJ-1 protects dopaminergic neurons against oxidative damage not only in vitro , but also in vivo (Bjorkblom et al 2013 ; Choi et al 2014 ; Mullett et al 2013 ; Tanti and Goswami 2014 ). Oxidised DJ-1 was shown to be significantly decreased in idiopathic PD brain, suggesting altered complex function controlled by DJ-1 may also play a role in the more common sporadic form of the disease (Piston et al 2017 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%